Starchy tuberos in the State of São Paulo: Commercialization channels and economic importance (Research, Society and Development, 2021)
Starchy vegetables are of great importance for food safety as well as alternative sources of energy. The objective of this study was to evaluate the economic importance of the amylaceous tuberous vegetables for the São Paulo state, Brazil. Thus, a survey of information was carried out in the databases of research institutions and governmental companies aiming to obtain information regarding the values of production, commercialization and also know the main channels used to distribution of these products. All the information obtained was discussed based on the social importance for the municipalities. The channels of commercialization studied were warehouses, government purchases and exports. The results showed that the warehouses are of great importance for the flow of fresh produce and that government purchases, besides boosting family farming, contribute to increase the value added of the products through the commercialization of processed products and the diversification of production, which sometimes contributes for the feeding of the family. We also observed that the amylaceous tuberous are of great social importance to the municipalities of Tapiraí and Piedade, since they are the main suppliers to the warehouses of São Paulo and agriculture accounts for more than half of the population's labor occupation. Foreign trade also proved to be an important way to trade, not only for the volume of products sold, but also for the greater added value. The results also showed that there are still products that do not have a structured production chain, such as arrowroot and tannia, but which are of great importance for some traditional communities.